(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
The discovery of the Celtiberian name GVANDOS in Latin epigraphy has demonstrated that it was not exclusive to Peñalba de Villastar. A review of Latin inscriptions from the present-day province of Cuenca has led to the identification of two additional attestations, confirming a broader geographical distribution and revealing closer ties between Celtiberian communities in Cuenca and Peñalba de Villastar. The study also sheds light on the sanctuary’s presumed frontier role and contributes to refining the chronology of the inscriptions from Peñalba. Finally, GVANDOS is definitively classified as an -o stem anthroponym, settling the longstanding debate over its value as an appellativum.